Interactive Association of Negative Creative Thinking and Malevolent Creative Thinking - Dou, Xinyu; Dou, Xinyan; Jia, Lin (Frontiers in Psychology, 2022)
With the existing research available on negative and malevolent creativity, this paper proposes a more narrowly defined concept: the bi-directional relationship between negative and malevolent creative thinking, which is intended to clarify the way forward for research in the area of negative and malevolent creativity. This paper uses qualitative research to identify and correlate an individual's concept of negative and malevolent creativity and uses a Inductive reasoning methodology to outline a preliminary theory.Following this, the preliminary theory was returned to the primary sources for validation, continuous optimization, and presentation.To better demonstrate the bidirectional linkage mechanism of thinking between the two types, this paper constructed a model to describe the relationships between the variables.This study concludes that negative creative thinking is a kind of native thinking based on personal interests that are developed to emphasize the benefits of an individual's interests, while malevolent creative thinking is a kind of native thinking based on the value-added of personal interests and is deliberately harmful. Both types of thinking share a value orientation, environmental stimulation, and subjective motivation.However, they differ in terms of value goals, ways of thinking, and the scale of the subject. It is concluded from the intrinsic thinking logic of individual thinking as well as the temporal dimension of the individual creative process that value-added and intentions to exploit others are factors that drive the transformation of negative creative thinking into malevolent creative thinking, and personal intention is a vital factor for establishing a linkage between negative and malevolent creative thinking.